Early Amyloid Detection in Idiopathic Carpal Tunnel Syndrome: A Puzzling Gap Between Peripheral and Cardiac Involvement - Ana Martins; Raquel Machado; Sofia Pimenta; Janete Santos; Hugo Osório; Pedro Madureira; Francisco Serdoura; Elsa Fonseca; Barbara Pereira; Lúcia Costa; Elisabete Martins (Journal of Clinical Medicine, 2026)
Background/Objectives: Idiopathic Carpal Tunnel Syndrome (CTS) can be an early manifestation of systemic amyloidosis, particularly transthyretin cardiac amyloidosis (ATTR-CA). The primary purpose of this retrospective case series was to describe the presence of amyloid deposits in tenosynovial tissue and explore potential cardiac involvement in patients undergoing carpal tunnel release surgery. Methods: From a cohort of 54 patients diagnosed with bilateral idiopathic CTS with surgical indication, 12 patients were selected for tenosynovial tissue samples, which were subsequently evaluated using Congo red staining and proteomic confirmation via mass spectrometry. Before the procedure, patients underwent a clinical assessment of medical history, electrocardiogram, and cardiac scintigraphy with Technetium-99 m 3,3-diphosphono-1,2-propanodicarboxylic acid (99mTc-DPD). Transthoracic echocardiogram and cardiac magnetic resonance were subsequently performed in all patients with positive scintigraphy, while a subset of scintigraphy-negative patients underwent an echocardiogram. Results: Congo red staining identified amyloid deposits in 3 of the 12 patients (25%). Proteomic analysis confirmed ATTR amyloidosis deposits in 2 of these patients (17%). One of these 2 patients presented Perugini grade 3 uptake on cardiac scintigraphy, suspicious for ATTR-CA. Complete concordance across histology, proteomics, and cardiac imaging was observed in only 1 patient (8.3%). Three discordances were noted: one case of tenosynovial ATTR without evident cardiac disease, one patient with a discordant Congo red result likely reflecting low amyloid burden or tissue heterogeneity, and one with imaging findings suspicious for ATTR-CA despite a negative tenosynovial biopsy. Conclusions: Tenosynovial biopsy obtained during CTS surgery can reveal early amyloid deposition, which may precede overt cardiac involvement. The variability observed across findings underscores the need for a multimodal diagnostic approach that integrates histological, proteomic, and imaging data, thereby mitigating the risk of amyloidosis misclassification.